A Novel Educational Paradigm to Address Gaps in Antimicrobial Prescribing Knowledge, Attitudes, and Practices. (4th October 2017) - Salsgiver, Elizabeth; Martin, Elena; Simon, Matthew S; Greendyke, William; Zachariah, Philip; Saiman, Lisa; Furuya, E Yoko; Calfee, David P
Abstract: Background: Gaps in knowledge, attitudes, and practices (KAP) related to antimicrobial prescribing can be barriers to optimal antimicrobial use. A case-based educational program was developed to address barriers identified in a 2015 KAP survey. A novel paradigm was utilized to teach antimicrobial prescribing as a continuum in which frequent re-evaluation and the use of evidence-based practices are applied. Methods: 7 in-person educational sessions were administered across 3 tertiary academic medical centers in New York, New York. Attendees were medicine and pediatric housestaff. Adult- and pediatric-specific cases were developed. Commonly encountered clinical scenarios were used to address topics such as determining the need for and selection of empiric therapy, selecting an appropriate duration of therapy, interpreting antimicrobial susceptibility testing, de-escalating empiric therapy, and assessing reported penicillin allergies. Each session included ≥3 interactive clinical cases and incorporated an antibiotic prescribing paradigm titled "A.C.T." that included A ssessing the patient, C onsiderations for empiric therapy, and T argeting therapy. Throughout cases, A.C.T. was used to highlight concepts of appropriate antimicrobial use and re-evaluation of treatment, institutional resources, and guidelines. An anonymous program evaluation survey was administered after each session. Results: A total of 138 housestaff participated. After attending the presentation, 100% of participants indicated that they were more aware of available institutional resources, 91% were more likely to review the appropriateness of their patients' antibiotic regimens at 48–72 hours, and 99% agreed that periodic presentation of brief antibiotic teaching cases would be useful. In addition, 92% were more likely to incorporate the "A.C.T." philosophy into their practice. Conclusion: Case-based training of medicine and pediatric housestaff utilizing the A.C.T paradigm was well-received and accepted, increased awareness of available institutional resources, and may increase prescriber-initiated review of patient's antimicrobial regimens. Future research efforts will focus on program sustainability and assessing changes in antimicrobial prescribing practices. Disclosures: All authors: No reported disclosures.